Enhanced mechanical properties of ZrO2-Al2O3 dental ceramic composites by altering Al2O3 form. Issue 4 (April 2020) - Seo, Ji-Young; Oh, Daniel; Kim, Dae-Joon; Kim, Kwang-Mahn; Kwon, Jae-Sung
Highlights: Addition of Al2 O3 result in decrease in sintering shrinkage and relative density. Different forms of Al2 O3 in Al2 O3 –ZrO2 composite result in different mechanical properties. Addition of microfibre form Al2 O3 result in enhanced mechanical properties of Al2 O3 –ZrO2 . Addition of microfibre form Al2 O3 result in lowest Weibull modulus. Addition of greater than 20 vol% of microfibre form Al2 O3 result in agglomeration. Abstract: Objectives: This study evaluates the difference in physical and mechanical properties of ZrO2 ceramics, commonly used in dental applications, altered by three different forms of Al2 O3 content; microparticles (m), nanoparticles (n), and microfiber (f). Methods: Three different types of ZrO2 –Al2 O3 composites were formed using microparticle (m), nanoparticle (n), or microfibre (f) forms of Al2 O3 . The physical and mechanical properties such as sintering shrinkage, relative density, Vickers hardness, fracture toughness, and biaxial strength were evaluated. A Weibull analysis was performed to assess the strength reliability of the specimens. All data were calculated using the t-test and ANOVA. Results: The sintering shrinkage and relative density of all ceramic composite groups were decreased with the addition of Al2 O3 . The mechanical properties of ZrO2 –Al2 O3 (f) composite were higher than that of ZrO2 –Al2 O3 (m) composite and ZrO2 –Al2 O3 (n) composite. The maximum hardness, fracture toughness, and biaxial flexural strength were observed for 10 vol% of Al2 O3 fibre. When the content of Al2 O3 fibre in the matrix was increased above 20 vol%, agglomeration occurred and resulted in a decrease of hardness and toughness. The Weibull modulus value of the ZrO2 –Al2 O3 (f) composite was the lowest compared to that of other groups. However, characteristic strength (σ0 ) of ZrO2 –Al2 O3 (f) the highest value. Significance: The current study demonstrated that the addition of right amount of Al2 O3 microfibre into the ZrO2 matrix enhanced the mechanical properties of ZrO2 -Al2 O3 (f) composite, which would be favourable for dental applications.